Poultry meat and egg production - Parkhurst, Carmen R.; Mountney, George J. (New Delhi : CBS PUBLISHERS & DISTRIBUTORS, 1988)
This book is designed for those seeking an introduction to poultry science. Industrial practices covering science and production are described and are intended to be supplemented by lectures and laboratory instruction.
First Indian Reprint : 1997
Keywords: Poultry -- Breeding; Poultry -- Anatomy